The Implementation of Islamic Financial Literacy through “Kencleng” Program in School - Aisyah, I; Saepuloh, D (KnE Social Sciences, 2019)
Islamic financial literacy consists of 3 aspects, namely basic money management, financial planning, charity donation and zakat. One aspect of financial literacy is charity donation consisting of waqaf and sadaqah (alms). Islamic finance literacy is important to be understood and applied early so that students understand about the management of Islamic finance and has the characteristics of Muslims. Application of Islamic financial literacy in schools can be applied one of them through the activity called ”kencleng”. The purpose of this study is to describe the implementation of Islamic financial literacy, especially about alms through the program ”kencleng” in schools, as well as one application of character education for students. This kencleng program is done in SMK Lab School Tangerang. The method used is descriptive method. The results of this study indicate that most students have the level of understanding of Islamic financial literacy in the medium category that is equal to 81%. Behavior of charity ”kencleng” as my students is 63% or in fairly good category. It means the student who has good Islamic financial literacy has good enough behavior of alms ”kencleng” also in. Thus, this ”kencleng” program becomes an alternative to the application of Islamic financial literacy for students. Keywords: islamic financial literacy, alms (kencleng)